A Impact of Nuclear Radiation Exposure on Humans and Ecosystems: The Urgency of Iodine Pills in Emergency Management: A Literature Review - Arbani, Rafi Auliya Arbani; Seliana, Irma (Faculty of Medicine - Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Background: Nuclear disasters and radioactive contamination pose severe health and environmental risks, with both immediate and long-term effects. Beyond acute radiation sickness, exposure increases the risk of genetic mutations, thyroid cancer, cardiovascular diseases, and immune suppression. Radioactive isotopes like iodine-131 (I-131), cesium-137 (Cs-137), and strontium-90 (Sr-90) persist in ecosystems, bioaccumulate, and contaminate food chains. Iodine pills play a crucial role in blocking I-131 absorption by the thyroid, reducing thyroid cancer risk. Objective: This study evaluates iodine prophylaxis as a primary intervention in nuclear disasters and examines the cascading effects of environmental contamination. Methods: A systematic review was conducted using PubMed, Scopus, and Google Scholar with keywords like “nuclear disaster,” “radiation exposure,” and “potassium iodide pills.” Seven Scopus-indexed journals were analyzed, focusing on nuclear disaster preparedness, radiation effects, and iodine pill efficacy. Discussion: Elevated I-131 levels heighten thyroid cancer risks, making iodine pills essential. Rapid distribution and public awareness are critical, especially for vulnerable populations. Contaminated food chains pose long-term health risks, necessitating decontamination, radiation surveillance, and bioremediation to mitigate environmental damage. Conclusion: Immediate iodine prophylaxis, environmental remediation, and continuous health monitoring are vital for reducing nuclear disaster risks. A multidisciplinary approach involving governments, healthcare professionals, and environmental experts is essential for effective preparedness and response strategies.